Cells with Stochastically Increased Methyltransferase to Restriction Endonuclease Ratio Provide an Entry for Bacteriophage into Protected Cell Population - Ispolatov, y (Oxford University Press, 2022)
The action of Type II restriction-modification (RM) systems depends on restriction endonuclease (REase), which cleaves foreign DNA at specific sites, and methyltransferase (MTase), which protects host genome from restriction by methylating the same sites. We here show that protection from phage infection increases as the copy number of plasmids carrying the Type II RM Esp1396I system is increased. However, since increased plasmid copy number leads to both increased absolute intracellular RM enzyme levels and to a decreased MTase/REase ratio, it is impossible to determine which factor determines resistance/susceptibility to infection. By controlled expression of individual Esp1396I MTase or REase genes in cells carrying the Esp1396I system, we show that a shift in the MTase to REase ratio caused by overproduction of MTase or REase leads, respectively, to decreased or increased protection from infection. Consistently, due to stochastic variation of MTase and REase amount in individual cells, bacterial cells that are productively infected by bacteriophage have significantly higher MTase to REase ratios than cells that ward off the infection. Our results suggest that cells with transiently increased MTase to REase ratio at the time of infection serve as entry points for unmodified phage DNA into protected bacterial populations. © 2022 The Author(s). Published by Oxford University Press on behalf of Nucleic Acids Research.